Hubungan Beban Kerja Dengan Kinerja Perawat - Erwanto; Bernadeta Leviana; Nadhifah Rahmawati; Putu Sintya Arlinda Arsa (Journal Scientific of Mandalika (JSM) e-ISSN 2745-5955 | p-ISSN 2809-0543, 2025)
Nurses face many problems because they have many roles and responsibilities in providing services in hospitals. One of them is the excessive workload. Workload can cause stress, which leads to fatigue at work and physical or mental exhaustion, which can affect nurses' performance when providing services. The purpose of this study is to determine whether there is a relationship between the performance of nurses at "X" Hospital in Malang City and their workload. This study uses a cross-sectional method and a simple random sampling design, with a sample consisting of 30 nurses. data collection through questionnaires sent via Google Forms. There is a significant correlation between the performance of nurses at hospital "X" in Malang and their workload, according to the results of bivariate data analysis using the Spearman Rank (Rho) test with a significant value of r = 0.041